Development of high throughput screening assays and pilot screen for inhibitors of metalloproteases meprin α and β. Issue 5 (September 2014) - Madoux, Franck; Tredup, Claudia; Spicer, Timothy P.; Scampavia, Louis; Chase, Peter S.; Hodder, Peter S.; Fields, Gregg B.; Becker‐Pauly, Christoph; Minond, Dmitriy
ABSTRACT Zinc metalloproteinases meprin α and meprin β are implicated in a variety of diseases, such as fibrosis, inflammation and neurodegeneration, however, there are no selective small molecule inhibitors that would allow to study their role in these processes. To address this lack of molecular tools, we have developed high throughput screening assays to enable discovery of inhibitors of both meprin α and meprin β and screened a collection of well characterized pharmaceutical agents (library of pharmaceutically active compounds, n = 1, 280 compounds). Two compounds (PPNDS, NF449) confirmed their activity and selectivity for meprin β. Kinetic studies revealed competitive (PPNDS) and mixed competitive/noncompetitive (NF449) inhibition mechanisms suggesting that binding occurs in meprin β active site. Both PPNDS and NF449 exhibited low nanomolar IC50 and Ki values making them the most potent and selective inhibitors of meprin β reported to the date. These results demonstrate the ability of meprin α and β assays to identify selective compounds and discard artifacts of primary screening. © 2014 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 396–406, 2014.